Dossiê campo de públicas no Brasil: definição, movimento constitutivo e desafios atuais - Pires, Valdemir Aparecido [UNESP]; Silva, Suylan de Almeida Midlej e; Fonseca, Sergio Azevedo [UNESP]; Vendramini, Patrícia; Coelho, Fernando de Souza (My University, 2014)
This article introduces the Public’s Field, which brings together teachers and students of undergraduate courses in Public Administration, Public Management, Public Policy, Public Management and Social Policy in Brazil, around the republican and democratic ethos as values, and multidisciplinary approach as proposed construction of knowledge. Based on a literature review, documental analysis, and especially in participant observation of the authors as actors in the construction Field, the article is per se a dossier. It starts with the definition of the Field and describes - in detail - their constituent movement in the last 12 years, culminating in the approval of the National Curriculum Guidelines of Public Administration in 2013. The text shows the achievement and growth of Field in the country before the growing supply of undergraduate courses, stimulated by upgrading and expansion of the public sector. Finally, we list some challenges, concerning the process of institutionalization and identity.

Este artigo apresenta o Campo de Públicas, que congrega professores e estudantes dos cursos de graduação em Administração Pública, Gestão Pública, Gestão de Políticas Públicas, Gestão Social e Política Públicas, no Brasil, em torno do ethos republicano e democrático como valores, e da visão multidisciplinar como proposta de construção do conhecimento. Baseado em pesquisa bibliográfica, análise documental e, sobretudo, na observação participante dos autores como atores na construção do Campo, o artigo é per se um dossiê. Inicia-se com a definição do Campo e descreve – pormenorizadamente – seu movimento constitutivo nos últimos 12 anos, que culminou na homologação das Diretrizes Curriculares Nacionais de Administração Pública, em 2013. O texto mostra a concretização e o crescimento do Campo no país, diante da crescente oferta do ensino de graduação, perante a revalorização e a ampliação do setor público no país. Ao final, elencam-se alguns desafios, concernentes ao seu processo de institucionalização e identidade.
Keywords: Undergraduate Studies; Public Sector; National Curriculum Guidelines for Public Administration; ENEAP; Area of Multidisciplinary Knowledge; Ensino de Graduação; Setor Público; Diretrizes Curriculares Nacionais de Administração Pública; ENEAP; Área de Conhecimento Multidisciplinar